(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This article analyzes the quality of the credit portfolio and risk management practices in commercial banks. It examines the key factors influencing credit portfolio quality, including credit risk assessment, diversification strategies, and the effectiveness of monitoring mechanisms. The study highlights modern approaches used in banking practice to identify, evaluate, and mitigate credit risks, as well as methods for reducing non-performing loans and improving asset quality. Furthermore, the paper explores institutional and regulatory frameworks that support effective credit portfolio management, emphasizing their role in ensuring financial stability and operational efficiency of commercial banks. Based on analytical findings, the article identifies priority directions for strengthening credit portfolio quality and enhancing risk management systems. The study also provides practical recommendations for applying advanced banking practices to improve the resilience and sustainability of commercial banks in a competitive financial environment.